Entrepreneurship Education Training for Teachers of SMK Muhammadiyah 3 Gresik - Heri Cahyo Bagus; Aries Kurniawan (OJS Universitas Muhammadiyah Gresik, 2023)
PKM is carried out at a school in Gresik Regency, namely SMK Muhammadiyah 3 Gresik Regency is one of the SMK education that develops entrepreneurship education for its students. From a geographical perspective, it is located on the outskirts of Gresik, precisely on Jl. Raya Morowudi No.141 Cerme District, Gresik Regency. When secondary education such as SMA/MA/SMK develops work skills, such as providing practice facilities for Electric Power Installation Engineering, Light Vehicle Engineering and Computer and Network Engineering, it is necessary to build an entrepreneurship ecosystem to realize the vision and mission of the institution so that it not only understands the technique but also needs to build an entrepreneurial character. So that graduates can have expert practitioners in the field of electrical engineering but who have an entrepreneurial spirit. Computer network techniques are encouraged to have entrepreneurial insight and character. Ilham et.al, 2020 said entrepreneurship is the key to success. And the teacher is the key to the success of it all. For this reason, through the Community Service Program (PKM) organized by Muhammadiyah Gresik University, it is hoped that teaching teachers and practicum teachers will gain entrepreneurial knowledge, develop their entrepreneurial character and understand entrepreneurial management to be taught to students. Entrepreneurship education not only provides a theory about the concept of entrepreneurship but also forms the attitude, behavior and mindset of entrepreneurs (Setiawan, Hidayat, et.al, 2022).The results of the implementation of the entrepreneurship education training program for teachers at SMK Muhammadiyah 3 Gresik Regency are: (1) the mindset and insights of teachers in the field of entrepreneurship are awakened; (2) the establishment of an entrepreneurial-oriented learning model and curriculum design, and; (3) offering advanced coaching solutions for teachers in the field of entrepreneurship as well as an industrial safari program as one of the efforts to realize the school's vision and mission with the target of graduates having an entrepreneurial spirit and character, ready to become entrepreneurs and become Islamic entrepreneurs.